Clinicopathological study of peripheral odontogenic fibromas (WHO-type) in Malaysians (1967-95) - Siar, C.H.; Ng, K.H. (Elsevier, 2000)
Analysis of case records of 46 patients with peripheral odontogenic fibroma (1967-95) diagnosed in the Division of Stomatology, Institute for Medical Research, Kuala Lumpur, disclosed a relatively young age of onset (mean, 32.2 Sears; range 5 months-64 years; peak incidence second decade of life), a slight female preponderance (M:F ratio 1:1.3), no racial predilection, a slight bias towards location in the mandible (52) and a wide histomorphological range. All cases were treated by simple excision, Follow-up records mere generally not available, so we do not know what the recurrence rate is.